Tinjauan Yuridis Keterangan Saksi dalam Penyelidikan dan Penyidikan Perkara Tindak Pidana Narkotika di Lembaga Perlindungan Saksi dan Korban (Lpsk) - Harahap, Abdul Muikhwal; Ahmad, Akiruddin; Joharsah, Joharsah (Innovative: Journal Of Social Science Research, 2024)
This research aims to examine the juridical review of witness statements in the process of investigating and investigating narcotics crimes which are under the protection of the Witness and Victim Protection Agency (LPSK). In the criminal justice system, witness statements play an important role in the law enforcement process, especially in uncovering and proving narcotics crimes. However, witnesses often experience intimidation or threats, so adequate protection is needed. LPSK exists as an institution that has an important role in providing legal protection for witnesses and victims of crime. This research uses a normative juridical approach by examining related laws and regulations as well as case studies of several narcotics crime cases involving witness protection by the LPSK. The research results show that witness statements protected by LPSK have the same legal force as witnesses in general, however there are several obstacles in implementing protection, both in terms of coordination between institutions and limited resources. Therefore, it is necessary to optimize the function of the LPSK in the inquiry and investigation process so that the effectiveness of witness protection can be achieved optimally.